2016
DOI: 10.1155/2016/3073908
|View full text |Cite
|
Sign up to set email alerts
|

Male Partner’s Involvement in HIV Counselling and Testing and Associated Factors among Partners of Pregnant Women in Gondar Town, Northwest Ethiopia

Abstract: Background. Despite the existence of several programmes promoting male involvement in HIV counselling and testing during their wife's pregnancy as a part of PMTCT, few men have heeded the call. The aim of this study was to assess male partner's involvement in HCT and its associated factors. Methods. This study was based on institution based cross-sectional study design that used systematic random sampling technique. A total of 416 partners were interviewed in the data collection. Multivariable logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 11 publications
9
32
1
Order By: Relevance
“…17, 5.14). This finding is consistent with a previous studies conducted at Mekele, Northern Ethiopia and Arba Minch town and Zuria Woreda, Southern Ethiopia [8,11]. This could be due to the fact that their partners did not tell the need to go with them and utilize PMTCT services might failed to appreciate the importance of males' involvement for prevention HIV infection from mother to child.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…17, 5.14). This finding is consistent with a previous studies conducted at Mekele, Northern Ethiopia and Arba Minch town and Zuria Woreda, Southern Ethiopia [8,11]. This could be due to the fact that their partners did not tell the need to go with them and utilize PMTCT services might failed to appreciate the importance of males' involvement for prevention HIV infection from mother to child.…”
Section: Discussionsupporting
confidence: 91%
“…The study result revealed that 21.2%, (95%CI 17.8%, 24.8%) of males were involved in PMTCT of HIV program. Our finding is comparable with a previous studies reported from Gondar town, North west Ethiopia, and Mekelle, Northern Ethiopia 20.9% and 20%, respectively [10,11]. This implies that male participation in PMTCT of HIV is poor.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Table 2 identifies basic characteristics of study setting and type of the included studies. Of the 44 articles included, 24 were qualitative studies [ 13 , 14 , 18 23 , 25 , 27 , 28 , 39 51 ], 10 were cross sectional studies [ 26 , 51 59 ], 3 were cohort studies [ 24 , 60 , 61 ], 3 were systematic reviews [ 12 , 16 , 17 ], 3 were randomised control trials [ 62 64 ], and 1 used mixed methods [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Ethiopia, where the proportion of men who have been tested for HIV is as low as of 15% (21) especially in rural area, the male partner reception of HIV testing and counseling also remained to be low where only one fourth (24.7%) of mothers have their partners screened for HIV at ANC (22). The male partner involvement in PMTCT is found to be less in low-middle income countries including Ethiopia where only about 40%-50% of women have their partners participate in PMTC (23,24). However, great effort is put on strengthening the PMTCT services among HIV positive women in Ethiopia, less is known about the reason for the less or non-involvement of male partners in the service.…”
Section: Introductionmentioning
confidence: 99%